The Importance of the Manufacturing Sector in the Romanian Economy. (2016) - Herman, Emilia
Abstract: A series of recent research [5, 15, 16, 27] highlight the fundamental idea that the manufacturing sector represents a cornerstone of many national economies, a crucial sector to the generation of structural change, productive jobs and sustainable economic growth. The aim of this paper is to highlight the place and role of the Romanian industry, especially the manufacturing sector, in the national economy and its impact on employment and sustainable development. The results of this research show that, Romania has entered a process of deindustrialization for over two decades. After 2000, the intensity of the deindustrialization process decreased which allowed manufacturing to remain the backbone of the Romanian industry and whole economy. A real challenge of the Romanian manufacturing is the low level of labour productivity and low level of medium and high-technology manufacturing activities. In order to increase the resilience of the Romanian economy in the context of economic globalizations and to assure sustainable economic growth and development a reindustrialization through sustainable and productive manufacturing is necessary.